Pemberdayaan Jama’ah Masjid Al-Ihya Cigugur Kabupaten Kuningan Pada Masa Pandemi Covid 19 - Sihabudin Zuhri; Agus Lili Suhali; Khaerul Wahidin; Muhammad Azka Maulana (AL-MUFASSIR, 2020)
The development of mosque congregations in the midst of the Covid-19 pandemic is a challenge for the mosque prosperity council (DKM). Empowerment in terms of health, the economy is very important, especially since the arrival of the corona virus has crippled the economy of the Indonesian people and clearly has a major impact on the religious sector, especially in mosques. The purpose of this research is to find out how the empowerment of mosque congregations in dealing with the impact of Covid 19. The method used in this study is a qualitative descriptive method that seeks to describe a social phenomenon. In other words, this study aims to provide complete information so that it is beneficial for the development of science and can be applied more to various problems. In addition, the empowerment of the Al-Ihya mosque congregation in dealing with Covid-19 which is adjusted to the stages of qualitative research which is divided into three fields, namely, empowerment in the health, economy and religion sectors. So that with this empowerment program carried out by DKM Al-Ihya it is expected to provide mutual comfort.